The circulation and thermal structure of False Bay: a process-oriented numerical modelling and observational study - Nicholson, Sarah-Anne (Department of Oceanography, 2026)
False Bay, the largest bay in South Africa, lies between two of the world's most in-fluential current systems: the Agulhas and Benguela Current Systems. False Bay is situated at a biogeographic break (Pitcher et al., 2010), belonging to both the South-ern Benguela upwelling system and the Western Agulhas Bank. The oceanography of Southern Africa, particularly this region, is some of the most complex and highly variable in the world (Roberts, 2005). Owing to the surrounding steep orography and its position, the meteorology of the False Bay region is also complex, having wind con-ditions that are unique when compared to other regions of South Africa (Jury, 1991). It is under these special conditions that the circulation of False Bay is regarded as highly complex.